Atypical Fusion Peptide of Nelson Bay Virus Fusion-Associated Small Transmembrane Protein - Cheng, LiTing T. (American Society for Microbiology, 2005)
A 10-kDa nonstructural transmembrane protein (p10) encoded by a reovirus, Nelson Bay virus, has been shown to induce syncytium formation (34). Sequence analysis and structural studies identified p10 as a type I membrane protein with a central transmembrane domain, a cytoplasmic basic region, and an N-terminal hydrophobic domain (HD) that was hypothesized to function as a fusion peptide. We performed mutational analysis on this slightly hydrophobic motif to identify possible structural requirements for fusion activity. Bulky aliphatic residues were found to be essential for optimal fusion, and an aromatic or highly hydrophobic side chain was found to be required at position 12. The requirement for hydrophilic residues within the HD was also examined: substitution of 10-Ser or 14-Ser with hydrophobic residues was found to reduce cell surface expression of p10 and delayed the onset of syncytium formation. Nonconservative substitutions of charged residues in the HD did not have an effect on fusion activity. Taken together, our results suggest that the HD is involved in both syncytium formation and in determining p10 transport and surface expression.